Probing the mechanisms of action and resistance of mixed-ligand platinum(II) complexes with dual-stage antiplasmodium activity - Ishmail, Fatima-Zahra (Department of Chemistry, 2025)
Malaria remains one of the largest parasitic disease burdens worldwide, with the vast majority of that burden occurring on the African continent. The ongoing high number of malaria cases and deaths is in part attributable to the emergence and spread of resistance to most clinical chemotherapeutics. With the reported development of partial resistance to the current front-line artemisinin-based combination therapies, there is an increased risk of malaria morbidity and mortality as limited replacement treatments are currently available. For that reason, it is essential to invest in the discovery of compounds with novel mechanisms of action (MoA), dual-stage activity, and with immutable targets. Until now, drug discovery has typically focused on the development of antimalarials that are entirely organic in composition. This has left the field of inorganic medicinal chemistry and transition metal-based chemotherapeutics underexplored and underrepresented.